Sickle cell disease and malaria: decreased exposure and asplenia can modulate the risk from Plasmodium falciparum - Mwaiswelo, Richard O. (Malar J, 2020)
BACKGROUND: Patients with sickle cell disease (SCD), an inherited haemoglobinopathy, have increased risk of malaria, at least in part due to impaired splenic function. Infection with Plasmodium falciparum in SCD patients can trigger painful vaso-occlusive crisis, increase the severity of anaemia, and contribute to early childhood mortality. CASE PRESENTATION: A 17 year-old Tanzanian male with known SCD was admitted to Muhimbili National Hospital, a tertiary referral centre in Dar-es-Salaam, following an attack of malaria. From 2004 to 2007 the patient had lived in USA, and from 2010 to 2016 in France where, on account of hypersplenism and episodes of splenic sequestrations, in 2014 the spleen was removed. After appropriate clinical and laboratory assessment the patient was re-started on hydroxyurea; and anti-malarial-prophylaxis with proguanil was instituted. The patient has remained well and malaria-free for the following 15 months. CONCLUSION: SCD patients are highly vulnerable to malaria infection, and impaired splenic function is a feature of SCD patients, even in those who still anatomically have a spleen. This patient had a surgical splenectomy and, in addition, had probably lost some of the acquired malaria-immunity by having lived for several years in malaria-free areas. This patient is a compelling reminder that long-term anti-malarial prophylaxis should be offered to all patients with SCD who live in malaria-endemic areas.